Pengaruh Electronic Word of Mouth (e-WOM) terhadap Purchase Intention yang Dimoderasi Kualitas Produk - Aqsya Shaqilla; Hendrati Dwi Mulyaningsih; Nindya Saraswati (UNISBA Press, 2024)
Abstract. This research focuses on electronic word of mouth, purchase intention, and product quality. The purpose of this study to determine the relationship between electronic word of mouth and purchase intention and the role of product quality as a moderating variable in Kalamula Kopitiam on Tiktok Social Media. The method used in this study is a survey method through questionnaires as a data collection technique. The objects in this study were visitors to Kalamula Kopitiam, using a total sample of 100 people. The sampling technique used in this study was random sampling. There are two hypotheses in this study. To test the hypothesis, the techniques used are simple regression analysis and MRA (modified regression analysis). The results of this study indicate that there is a positive and significant influence of electronic word of mouth (e-WOM) on purchase intention at Kalamula Kopitiam on Tiktok social media. Furthermore, product quality strengthens the relationship between electronic word of mouth and purchase intention at Kalamula Kopitiam on Tiktok social media. Abstrak. Penelitian ini berfokus pada variabel electronic word of mouth, purchase intention, dan kualitas produk. Penelitian ini bertujuan untuk mengetahui hubungan antara electronic word of mouth dan purchase intention serta peran kualitas produk sebagai variabel moderasi pada Kalamula Kopitiam di Sosial Media Tiktok. Metode yang digunakan pada penelitian ini adalah metode survei melalui kuesioner sebagai teknik pengumpulan data. Objek pada penelitian ini adalah pengunjung Kalamula Kopitiam dengan menggunakan jumlah sampel sebanyak 100 orang. Teknik sampling pada penelitian ini menggunakan random sampling. Terdapat dua hipotesis yang ada pada penelitian ini. Untuk menguji hipotesis, teknik yang digunakan yaitu analisis regresi sederhana dan MRA (Moderated Regression Analysis). Hasil dari penelitian ini menunjukan bahwa terdapat pengaruh positif dan signifikan antara electronic word of mouth (e-WOM) terhadap purchase intention pada Kalamula Kopitiam di Sosial Media tiktok. Selanjutnya, kualitas produk memperkuat hubungan antara electronic word of mouth terhadap purchase intention pada Kalamula Kopitiam di Sosial Media Tiktok.